2013
DOI: 10.1590/s0100-204x2013000800048
|View full text |Cite
|
Sign up to set email alerts
|

Efeito anestésico do eugenol em juvenis de pacamã

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito do eugenol como anestésico para juvenis de pacamã (Lophiosilurus alexandri). Os animais foram divididos em dois grupos, denominados juvenil I (0,72 g) e juvenil II (7,44 g), e submetidos a seis tratamentos de eugenol (20, 40, 60, 80, 100 e 120 mg L -1 ), em dez repetições. Durante o experimento, foram realizadas biometrias e cronometragens dos tempos de indução e recuperação. Com o aumento das doses, o tempo de anestesia foi reduzido de 69 para 27 s, em ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…Regression curves obtained for all assays in the present study had a pattern similar to those established by other authors for eugenol (Vidal et al, 2007;Bernardes Júnior et al, 2013;Ribeiro et al, 2013) and for tricaine (Pawar et al, 2010), indicating a marked decrease in induction time between lower concentrations and a tendency toward stability as doses increase. Furthermore, the standard deviation was inversely proportional to the doses tested, of which the lowest values of standard deviation were shown with the highest dosages.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Regression curves obtained for all assays in the present study had a pattern similar to those established by other authors for eugenol (Vidal et al, 2007;Bernardes Júnior et al, 2013;Ribeiro et al, 2013) and for tricaine (Pawar et al, 2010), indicating a marked decrease in induction time between lower concentrations and a tendency toward stability as doses increase. Furthermore, the standard deviation was inversely proportional to the doses tested, of which the lowest values of standard deviation were shown with the highest dosages.…”
Section: Resultssupporting
confidence: 89%
“…The same study suggested that 98 mg L -1 of eugenol induces anesthesia in 1 minute based on the calculated regression model. Other regression models estimated that a concentration of 24 mg L -1 of eugenol is sufficient to induce anesthesia for pacamã (Lophiosilurus alexandri) juveniles (7.44 ± 0.44 g) at one minute (Ribeiro et al, 2013), whereas anesthesia of the snook (Centropomus undecimalis) (7.63 ± 0.15 g) at one minute was estimated to require 117 mg L -1 of this compound (Bernardes Júnior, Nakagome, Mello, Garcia, & Amaral Júnior, 2013). These results show that the pearl cichlid is resistant to eugenol when compared to other species (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Eugenol is a natural product obtained from the distillation of the extract of clove (Eugenia caryophyllata) leaves, stems, and roots . The efficiency of eugenol has been observed for several species, such as rainbow trout (Oncorhynchus mykiss; Keene et al, 1998), pacamã (Lophiosilurus alexandri; Ribeiro et al, 2013), Nile tilapia (Oreochromis niloticus; Vidal et al, 2008;Ribeiro et al, 2015b), matrinxã (Brycon cephalus; Barbosa et al, 2007;Vidal et al, 2007), pacu (Piaractus mesopotamicus; Gonçalves et al, 2008), lambari (Astyanax altiparanae; Pereira-da-Silva et al, 2009), silver catfish (Rhamdia quelen; Cunha et al, 2010;Gomes et al, 2011), and fat snook (Centropomus parallelus; Souza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Para os outros estágios de sedação, exceto para a permanência no estágio normal, quanto maior foi à dose, menor foi o tempo de permanência nos estágios avaliados, fenômeno constatado também em outros experimentos que utilizaram o eugenol como anestésico para outros peixes (Façanha and Gomes, 2005;Souza et al, 2012;Ribeiro et al, 2013). Este efeito está relacionado ao fato de a solução de eugenol (10 %) ser adicionada na água e quanto maior a dose, maior será a concentração do anestésico na água, o que potencializa o efeito do sedativo acelerando a anestesia completa e reduzindo o tempo de permanência nos estágios de sedação intermediários.…”
Section: Doseunclassified